Bipolar disorders and creativity: the roles of ambition, effort-based decision-making, and exploration - Tse, Samson; Johnson, Sheri L.; Yu, Chong Ho; Yuen, Winnie; Lo, Iris; Clark, Luke; Michalak, Erin E.; Ironside, Manon; Modavi, Kiana (Frontiers in Psychiatry, 2025)
IntroductionEpidemiological research has shown those with bipolar disorders (BD) are more likely to work in creative professions. The current work is the first to examine ambition, exploration versus exploitation ratio, and insensitivity to effort/rewards among individuals with and without BD in an Asian cultural context.MethodsWriters and visual artists from Hong Kong who were diagnosed with BD completed a questionnaire to assess lifetime creative accomplishments, a self-rated measure of ambition, and two laboratory-based tasks: the observe-or-bet task to detect exploration versus exploitation tendencies, and an effort discounting task to measure sensitivity to effort required and reward level.ResultsThe sample included 44 participants diagnosed with BD and 69 control participants, with 87 (77%) being female and an average age of 35.1 years (range: 18 to 65). Bayesian analyses found no group differences in creativity or related mechanisms between BD and control participants. However, decision tree algorithms revealed multivariate contributors to creative accomplishments. Replicating prior work, high ambition was key, with the most productive also willing to persevere despite high effort. Among lower-ambition individuals, control participants who engaged in balancing exploration versus exploitation had greater accomplishments. Importantly, there was no evidence that the effects of ambition or effort-based decision-making on creativity differed based on BD diagnosis. Bipolar group had lower socioeconomic status potentially impacting their self-rated creativity scores and creative potential. However, these findings remain tentative and await further investigation due to limited sample size.DiscussionThe findings suggest the mechanisms underlying creativity may not inherently differ for those with BD compared to controls. Ambition, especially when combined with effort and willingness, drives creative accomplishments. Strategic use of exploration versus exploitation was associated with greater creativity among less ambitious individuals without BD. A nuanced, multivariate approach is needed to understand the bipolar-creativity relationship across cultures. Study limitations included small sample size and over-representation of female participants.